Development of a transcutaneous form of desloratadine - Valentin P. Ageev; Andrey V. Zaborovskiy; Dina V. Yunina; Larisa A. Tararina; Mikhail K. Devkota; Dmitry N. Andreev; Aleksandra E. Pyanzina; Vasilisa I. Shlyapkina; Yulia A. Buldygina; Oleg A. Kulikov; Nikolay A. Pyataev (Belgorod National Research University, 2024)
Introduction: For people with allergies, it is not always possible to prevent allergens admission to the body. For this reason, it is essential to create a long-acting drug that can prevent an allergic reaction. The very promising option is a transdermal therapeutic system (TTS), with H1 blockers. The aim of the study: To create a technology for the production of desloratadine-based TTS, suitable for routine use with prolonged drug releasing. Materials and Methods: Polyvinylpyrrolidone K30 (PVP) was used as the main matrix polymer for TTS, and the Kruofilm polymer membrane was used as the adhesive layer. The formation of the polymer membrane was carried out by drying a water-alcohol solution of the components at a temperature of 60ºC. Characterization of the obtained dosage forms was made by spectrophotometry. The resulting micelles size was measured by dynamic light scattering. Results and Discussion: Round shaped TTS (patches) with water-dissolved desloratadine (DL) and its micellar form were obtained. The size of micelles with DL was 22.8±5.2 nm. The spectrophotometric method for determining DL has been developed. The containing of DL in the patches ranged from 5 to 25 mg per patch, depending on the manufacturing technology. Conclusion: We have developed TTSs containing DL by a solution and a micellar form. A top adhesive layer has been selected that has moisture resistance, strength and reliable fixation of the matrix with the active substance on the skin. A method for the spectrophotometric determination of DL in solutions and patches was developed and validated.